2011
DOI: 10.1111/j.1466-7657.2011.00897.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students' perceptions of nursing: a descriptive study of four cohorts

Abstract: Such results delineated the importance of revising nursing schools' curricula and the universities' admission policies into the nursing profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 24 publications
3
38
1
8
Order By: Relevance
“…At the beginning of the study, many students had idealistic perception of nursing, and the perception changed under the infl uence of educational program due to the infl uence of nursing theory and science, and clinical experience 17,18 . It is expected that during their study program, students acquire the necessary competence for independent, safe and quality nursing care, and that they develop professional identity.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of the study, many students had idealistic perception of nursing, and the perception changed under the infl uence of educational program due to the infl uence of nursing theory and science, and clinical experience 17,18 . It is expected that during their study program, students acquire the necessary competence for independent, safe and quality nursing care, and that they develop professional identity.…”
Section: Discussionmentioning
confidence: 99%
“…(Abdel El-Halem et al, 2001;Eman et al, 2012;Patidar et al, 2012) In Jordan, little is known about Jordanian student nurses' perception of nursing. (Safadi et al, 2011) Nursing students' perceptions of nursing might have an impact on their self-concept, self-esteem, recruitment, retention, and performance. (Wallace, 2007) Extrinsic reasons as pay and conditions of work which were previously hardly mentioned at all, have increasing importance.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Prospective nursing studies have investigated and defined changes in students' perceptions occurring over time. [12][13][14] Students' perceptions of nursing evolved from lay to professional images. Nursing studies suggest that these changes occur as a result of students' education.…”
Section: International Perspectivesmentioning
confidence: 99%
“…Nursing studies suggest that these changes occur as a result of students' education. [7] Safadi and colleagues [12] studied Jordanian nursing students' perceptions over 4 years of the nursing programme, and concluded that students' perceptions progressed from traditional altruistic beliefs to biomedical, technological perceptions. A Changing focus from caring to carrying out procedures was also identified by Pearcey [15] who reported that despite the new trends in nursing that advocate the move away from tasks and routines; holistic care remains a term that is followed by a list of physical tasks with no indications that this term is fully understood by students.…”
Section: International Perspectivesmentioning
confidence: 99%